PENGGUNAAN KATA KERJA SIMPLE PAST TENSE DAN ADJECTIVE DALAM PENULISAN TEKS RECOUNT - Fathurrahman Fathurrahman (Universitas Indraprasta PGRI, 2021)
The aim of the research is to know the use of simple past tense and adjective verbs ofSMPN in Central Jakarta in writing recount text and to find out what errors the most dominant students made. The research approach used in this study is a qualitative approach. After analyzing the students' writing, the writer gets the conclusion that 1) the most common types of mistakes in simple past tense are misformation at 67.99%. This error reached 189 errors out of a total of 278 errors. Meanwhile, the least type of misuse of is misordering by 3.96%. This error reached 11 errors out of a total of 278 errors. While the other types of errors were error of omission of 12.23% which reached 34 errors out of a total of 278 errors and error of addition of 9.71% which totaled 27 errors out of a total of 278 errors. 2) Errors in adjective writing were 17 errors or 6.11%.Keywords: simple past tense, recount text, EFL, junior high school